2016
DOI: 10.1186/s40780-016-0067-2
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of regional cooling for paclitaxel-induced peripheral neuropathy

Abstract: BackgroundThere are currently no promising therapies available to treat or prevent peripheral neuropathy (PN) induced by anticancer drugs in a cumulative dose-dependent manner. In this study, we investigated the efficacy of regional cooling of hands and feet in preventing paclitaxel (PTX)-induced PN.MethodsPatients with gynecologic cancer who received a tri-weekly cycle of chemotherapy including PTX at doses of 150–175 mg/m2 were included in this study. Regional cooling was performed by covering patient hands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 31 publications
0
42
1
4
Order By: Relevance
“…Several studies have employed frozen gloves as a mode of cryotherapy in preventing CIPN [4,8,9,14,23,29,31,32]. These studies have demonstrated frozen gloves are able to deliver considerable regional hypothermia, however, this effect is not sustained or stable thereby potentially reducing the efficacy of vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have employed frozen gloves as a mode of cryotherapy in preventing CIPN [4,8,9,14,23,29,31,32]. These studies have demonstrated frozen gloves are able to deliver considerable regional hypothermia, however, this effect is not sustained or stable thereby potentially reducing the efficacy of vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent trial reported by Hanai et al (2018), cryotherapy in the form of frozen gloves was effective in preventing and reducing the occurrence of CIPN [9]. Similarly, inspired by scalp cooling therapy to combat chemotherapy-induced alopecia (CIA) [7,15], several groups have demonstrated promising results that the use of frozen gloves and socks concomitantly with the chemotherapy infusion is efficacious in reducing CIPN [4,9,23,29,31,32]. However, latest reports indicate that the frozen gloves have been recalled due to incidences of frostbite and other patient safety issues [10].…”
Section: Introductionmentioning
confidence: 99%
“…The first evidence came as an explorative analysis, revealing that patients utilizing frozen gloves and socks for the prevention of docetaxel-induced nail toxicity experienced a 44% reduction in the risk of CIPN (13). Other studies have examined if similar benefits can be observed among patients receiving chemotherapy (14)(15)(16)(17)(18)(19)(20). However, the findings of these studies have been inconsistent, exemplifying the need for more confirmatory studies (21).…”
Section: Introductionmentioning
confidence: 99%
“…No serious adverse effects were associated with cryotherapy although one patient discontinued cryotherapy halfway through cycle 3 due to cold-induced pain. 21…”
Section: Resultsmentioning
confidence: 99%